Analysis of Screening and Rehabilitation Intervention Program for Student Drug Users at Badan Narkotika Nasional Provinsi Jawa Timur (BNNP JATIM) - Ihsan Ridho Ma'arief; Vania Ardelia (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Screening and rehabilitation intervention activities for students with drug abuse constitute a program implemented by Bidang Rehabilitasi Badan Narkotika Nasional Provinsi Jawa Timur. This research aims to understand the experience of screening and rehabilitation activities conducted among school student groups and primary clinic rehabilitation clients. This study employs a qualitative method with a phenomenological approach. Data were collected through interview and observation methods involving eight school students and young addiction counselors, as weel as previous research to support data validity. Case analysis used Brofenbrenner’s Ecological Theory to understand various relational contexts and their influence in shaping individuals. The study found that family environment factors, such as parenting styles and drug use within the family, are significant causes of drug abuse behavior among students. Additionally, the school environment, peer influence, and the normalization of deviant culture contribute to the emergence of negative drug abuse behavior among adolescents. Strengthening coordination between BNNP Jawa Timur, schools, families, and the social community is necessary to build a comprehensive support system.